Demokrasi dalam Islam Perspektif Al-Qur’an - Ahmad Abdus Salam Aura Rusyda; Arasyid Isnandar; Ahmad Badrul Amin; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
In the current era, many countries use a democratic system as the basis of their country. However, in Islam, this needs to be specified. So that many scholars question this democratic law. This study tries to discuss these contemporary problems with a qualitative method approach and uses the maudhu'i interpretation method in discussing related verses in the Qur'an. The verses discussed are verse 165 of sura al-Baqarah and verse 44 of sura al-Ma'idah. From the various interpretations used, surah al-Baqarah verse 165 discusses the regret of people who make rivals other than Allah Azza wa Jalla and they love those they follow as they love Allah. When in the afterlife, the person being followed is separated from the person following when they know the punishment of Allah Azza wa Jalla. As for surah al-Maidah verse 44, it discusses ruling other than what Allah sent down. In terms of democracy, many make this letter al-Maidah verse 44 as an argument. However, in reality, many people do not understand this verse so that many cases are based on this argument, even though what is related to disbelief requires detail. Based on the opinion of the scholars that the law of democracy is haram and even includes shirk. The perpetrators can be categorized into three, namely: infidels, tyrants, and fasiq according to the conditions they experience. So not necessarily declared infidel.